Combining Chemical and Photo-Fenton Solar Coagulation Processes in the Treatment of Real Wastewater from Paint Industry - da Silva, Larissa Ferreira; Barbosa, Andreia Daniane; Machado, Antonio Eduardo da Hora; Andrade, Leonardo Santos (Orbital: The Electronic Journal of Chemistry, 2019)
In this work are presented and discussed the results related to the obtaining of the best conditions for the treatment of a real paint wastewater by combining the chemical coagulation methods and solar photo-Fenton process. The best conditions for the coagulation-flocculation process involved the use of 8 mL of chemical coagulant (ferric chloride) for every 1.0 L of wastewater. At this condition, total removal of turbidity and color (visual inspection) of the wastewater were achieved. For the solar photo-Fenton process, the concentration of Fe2+ and H2O2 at 105 mg L-1 and 2.0 g L-1, respectively, resulted in the complete removal of organic matter and odor (olfactory perception). Therefore, the combined use of these techniques in the treatment of the real paint wastewater presented quite relevant results from the environmental standpoint, as evidenced by the reduction/elimination of important environmental parameters, with the real possibility of disposal and/or reuse proposals of treated water. DOI: http://dx.doi.org/10.17807/orbital.v11i2.1365